Tuhan dalam Buku Basic Concept of the Qur'an Karya Abul Kalam Azad - Ilmiyah, Dakhirotul (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2018)
This paper examines the concept of God according to Abul Kalam Azad as it is expressed textually in his book Basic Concept of the Quran. It further elaborates on how does Abul Kalam Azad understands the concept of Divinity and how does he construct it as a basic value of human life. He argues that the One was the very first of human belief in God. It was later that the initial belief in God took a retrogressive turn, where the common people attempt to bodying the Almighty Being into some attributes for the sake of analogy of their own qualities. This idea suggests that Azad was of the scholars who hold that the archeology of human belief in the divinity of God is originated from the belief in the One. Azad has also argued that both verses of QS. 10: 19 and QS. 2: 213, which literally refers to “one single community”, alluded to refer as “one religion”, which means “One God.” This type of language game played by Azad has significantly contributed to favor his idea on monotheism and the Oneness of God. Keywords: Abul Kalam Azad, Theology, God, Monotheism.